Multicentric, prospective observational data show sperm capacitation predicts male fertility, and cohort comparison reveals a high prevalence of impaired capacitation in men questioning their fertility. Issue 1 (July 2020) - Sharara, Fady; Seaman, Eric; Morris, Randy; Schinfeld, Jay; Nichols, Jennifer; Sobel, Michael; Lee, Annette; Somkuti, Stephen; Hirshberg, Steven; Budinetz, Tara; Barmat, Larry; Palermo, Gianpiero; et al.
Abstract: Research questions: Can a previously defined relationship between sperm capacitation and the probability of a man generating pregnancy within three cycles, prospectively predict male fertility in diverse clinical settings? A second study asked, what is the prevalence of impaired sperm fertilizing ability in men questioning their fertility (MQF), and does this relate to traditional semen analysis metrics? Design: In the multicentric, prospective observational study, data ( n = 128; six clinics) were analysed to test a published relationship between the percentage of fertilization-competent, capacitated spermatozoa (Cap-Score) and probability of generating pregnancy (PGP) within three cycles of intrauterine insemination. Logistic regression of total pregnancy outcomes ( n = 252) assessed fit. In the cohort comparison, Cap-Scores of MQF ( n = 2155; 22 clinics) were compared with those of 76 fertile men. Results: New outcomes ( n = 128) were rank-ordered by Cap-Score and divided into quintiles (25–26 per group); chi-squared testing revealed no difference between predicted and observed pregnancies ( P = 0.809). Total outcomes ( n = 252; 128 new + 124 previous) were pooled and the model recalculated, yielding an improved fit ( P < 0.001). Applying the Akaike information criterion found that the optimal model used Cap-Score alone. Cap-Scores were performed on 2155 men (with semen analysis data available for 1948). To compare fertilizing ability, men were binned by PGP (≤19%, 20–29%, 30–39%, 40–49%, 50–59%, ≥60%). Distributions of PGP and the corresponding Cap-Scores were significantly lower in MQF versus fertile men ( P < 0.001). Notably, 64% of MQF with normal volume, concentration and motility (757/1183) had PGP of 39% or less (Cap-Scores ≤31), versus 25% of fertile men. Conclusions: Sperm capacitation prospectively predicted male fertility. Impaired capacitation affects many MQF with normal semen analysis results, informing diagnosis versus idiopathic infertility.